2010
DOI: 10.1086/653570
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Rotavirus VP7 and VP4 Genotypes in Northwestern Nigeria

Abstract: The high numbers of mixed rotavirus infections highlight the multitude of enteric pathogens to which children in African countries are exposed. Data on circulating rotavirus strains serve to inform African government officials to the serious health threat posed by rotavirus in their respective countries and to document the diversity of strains before vaccine introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
47
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 47 publications
(72 reference statements)
11
47
3
Order By: Relevance
“…The VP7 gene or nineth segment of RV genome encodes a glycoprotein that forms the outer surface of the virion and induces neutralizing immune responses during RV infections. This gene, targeted by RT-PCR amplified an expected band of 1062 bp for pig and human RV's; 1011 bp for cow RV strains and further confirmed the presence of RV in the studied species as been evidenced earlier too [2,25]. Circulations of RV in different susceptible host in a single geographical region therefore generate a potential possibility of zoonosis and thus provokes for reassortment of the viral strains consequently causing severe menace to vaccine failure.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The VP7 gene or nineth segment of RV genome encodes a glycoprotein that forms the outer surface of the virion and induces neutralizing immune responses during RV infections. This gene, targeted by RT-PCR amplified an expected band of 1062 bp for pig and human RV's; 1011 bp for cow RV strains and further confirmed the presence of RV in the studied species as been evidenced earlier too [2,25]. Circulations of RV in different susceptible host in a single geographical region therefore generate a potential possibility of zoonosis and thus provokes for reassortment of the viral strains consequently causing severe menace to vaccine failure.…”
Section: Discussionsupporting
confidence: 75%
“…This clearly connotes that RV transmission from animal origin to human population is maximum in close setting. The discontinuous RNA-PAGE was employed for RV strain grouping and studies also reported that this technique is another mostly used gold standard test for RV detection in faeces [2,5,11,16,24]. Analysis of electrophoretic mobility of the 11 segments of RV dsRNA by PAGE corresponded to the basic pattern of 4:2:3:2 typical for group A rotavirus (RVA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies in developing countries have shown increased identification of a high proportion of rotavirus strains with unusual G/P combinations, which may have implications for vaccine efficacy [Gentsch et al, 2005;Santos and Hoshino, 2005;Todd et al, 2010]. Several studies conducted in Ghana, Ivory Coast and Nigeria, close neighbors of Burkina Faso, have reported the high incidence of unusual G/P genotype combinations with the emergence of G9 strains as important cause of gastroenteritis [Armah et al, , 2010aAkran et al, 2010;Aminu et al, 2010]. Currently, two rotavirus vaccines [Rotarix (GSK Biologicals, Rixensart, Belgium) and RotaTeq (Merck & Co. Inc., West Point, PA)] have been licensed and implemented in immunization programs for children in many countries in Americas and Europe [Ruiz-Palacios et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, the rotavirus species comprises at least 27 G types (according to the nt sequence of VP7) and 37 P types (according to the nt sequence of VP4) [8,9]. VP7 protein (glycoprotein) and VP4 protein (for protease-sensitive protein) elicit the production of neutralizing antibodies, define the antigenic specificities, referred to as G type (glycoprotein) and P type (protease-sensitive protein), respectively, and are the major antigens neutralizing immune responses during rotavirus infections [10].…”
Section: Introductionmentioning
confidence: 99%